Chromosome 1 amplification has similar prognostic value to del(17p13) and t(4;14)(p16;q32) in multiple myeloma patients: analysis of real-life data from the Polish Myeloma Study Group. Issue 9 (2nd September 2017) - Grzasko, Norbert; Hajek, Roman; Hus, Marek; Chocholska, Sylwia; Morawska, Marta; Giannopoulos, Krzysztof; Czarnocki, Krzysztof; Druzd-Sitek, Agnieszka; Pienkowska-Grela, Barbara; Rygier, Jolanta; Usnarska-Zubkiewicz, Lidia; Dytfeld, Dominik; et al.
Abstract: The study aimed to assess prognostic significance of del(13q14), del(17p13), t(4;14)(p16;q32), and amp(1q21) in newly diagnosed myeloma patients treated mostly with thalidomide-based therapies. All genetic abnormalities except del(13q14) were independent prognostic factors associated with shortened progression-free survival (PFS) and overall survival (OS). Patients with no abnormalities, one abnormality, and ≥2 abnormalities had a median PFS of 41.8, 17.0, and 10.0 months, respectively; a median OS was not reached, 48.0 and 23.3 months, respectively. According to the presence of amp(1q21), t(4;14)(p16;q32), and del(17p13) and the International Staging System (ISS), we stratified patients into low-risk, intermediate-risk and high-risk groups. A median PFS was 52.9, 25.6, and 10.0 months, respectively; a median OS was not reached, 64.0 and 25.0 months, respectively. In conclusion, our study confirmed the prognostic value of cytogenetic changes and showed that prognostic models based on ISS and cytogenetic studies should include not only del(17p13) and t(4;14)(p16;q32), but also amp(1q21).